Performance Evaluation of Rice Husk-Based Catalytic Converters: Emission Reduction and Minimal Engine Power Loss Verified by Dynamometer Test (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2025)
Catalytic converters (CCs) play a critical role in reducing exhaust emissions in motor vehicles. This study presents a sustainable solution by utilizing rice husk waste (RHW) to produce activated carbon, which is then fabricated into honeycomb-shaped catalytic converters with thickness variations of 10 mm, 15 mm, 20 mm, and 25 mm. Among these, the 15 mm-thick converter (CC15) exhibited the most effective emission reduction performance, achieving reductions of 78.33% in hydrocarbons (HC) and 48.23% in carbon monoxide (CO). To assess its impact on engine performance, a series of dynamometer tests were conducted, showing that the installation of CC15 led to less than a 6% decrease in both power and torque, which is considered acceptable for daily vehicle use. Furthermore, the air–fuel ratio (AFR) shifted from an average of 13.38 under standard conditions to 14.19 with CC15, indicating stable combustion. Acoustic evaluation also confirmed that the CC did not function as a noise suppressor, resulting in no significant alteration to engine acoustics. Overall, the CC15 demonstrates an effective balance between environmental performance and engine efficiency, offering a practical emission control solution based on locally sourced agricultural waste.